1991
DOI: 10.2307/1242814
|View full text |Cite
|
Sign up to set email alerts
|

Factor Demands in the U.S. Food‐Manufacturing Industry

Abstract: This paper analyzes the demand for labor, capital, and energy in the U.S. foodmanufacturing industry using Allen and Morishima elasticities of substitution. The demand for capital is more elastic than for labor and energy, and these production factors are substitutable, especially between capital and labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
4
11
0
1
Order By: Relevance
“…Material input is a substitute with capital, labor, and energy, while capital and energy are substitutes. Moreover, our qualitative results are consistent with Huang (1991) and Goodwin and Brester (1995), in that capital, labor and energy are net substitutes.…”
Section: Elasticity Of Substitution Estimatessupporting
confidence: 86%
See 2 more Smart Citations
“…Material input is a substitute with capital, labor, and energy, while capital and energy are substitutes. Moreover, our qualitative results are consistent with Huang (1991) and Goodwin and Brester (1995), in that capital, labor and energy are net substitutes.…”
Section: Elasticity Of Substitution Estimatessupporting
confidence: 86%
“…Indeed, the family of flexible functional forms, such as the translog and generalized Leontief, provide a second-order approximation to the true underlying (but unknown) technology (Chambers, 1988). The widespread application of the translog cost functional form, its application in related studies (e.g., Goodwin & Brester, 1995;Huang, 1991), and its flexible properties make this functional form a natural choice. The translog cost function used here is…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of effort has been directed at investigating water use in primary agriculture (Caswell and Zilberman 1985;Ogg and Gollehon 1989;Moore, Gollehon and Carey 1994). However, as recent studies of the manufacturing component of the agri-food industry show, researchers have neglected the role of water (Hazeldine 1991;Huang 1991;Goodwin and Brester 1995). Given the steady growth in exports from Canadian food processors (Statistics Canada 1995) and increasing concern in Canada over water conservation and international competitiveness (Agriculture and Agri-Food Canada 1996;Farid, Jackson and Clark 1997), this paper provides a timely assessment of current and potential water use by this sector.…”
Section: Introductionmentioning
confidence: 99%
“…Huang (1991) examined the U.S. food-manufacturing industry. Based on Allen and Morishima elasticities of substitution, the above study found that labor and capital are substitutable.…”
Section: Translog Estimationmentioning
confidence: 99%